Differential Analysis of perception of the development of values in Physical Education classes - López Chamorro, José María; González Ponce, Inmaculada; Amado Alonso, Diana; Leo Marcos, Francisco Miguel; Sánchez Oliva, David (FEADEF, 2012)
The aim of the current study was to assess pupils' perception on the development of values in Physical Education classes, testing whether sex, importance given to Physical Education and extracurricular sport practice level promote significant differences regarding those variables. Hence, 218 male and female pupils participated in the study, ranging in age from 11 to 19 years old. We made descriptive and frequency analysis of all variables, as well as analysis of variance to measure the differences with regard to independent variables. After results analysis, we emphasized the importance given to Physical Education as differentiating variable in the perception of the development of values, whereas sex promotes significant differences in tolerance and respect to others. Nevertheless, extracurricular sport practice level did not show significant differences in any variable. Lastly, results are discussed, emphasizing the importance of pupils to Physical Education as determinant variable about perception on the development of values.